Nomophobia and Related Factors in Students of a Faculty of Humanities and Social Sciences - Pirincci, Edibe; Karacorlu, Fatma Nur; Oguzoncul, Ayse Ferdane; Deveci, Suleyman Erhan (Galenos Publ House, 2021)
Objective: Nomophobia is defined as the involuntary fear experienced by the individual when he/she cannot access his mobile device or cannot communicate on the mobile device. This study aimed to examine nomophobia and related factors in the first-and fourth-year students in the Department of Turkish Language and Literature and Western Languages and Literatures at the Faculty of Humanities and Social Sciences of Firat University. Methods: In this cross-sectional study, a questionnaire survey including questions about sociodemographic features and smartphone use and nomophobia questionnaire (NMP-Q) was performed. Results: Data were collected from 325 participants (69.2% female), with an average age of 21.06 +/- 3.54 years. The NMP-Q score was 73.21 +/- 26.60 points. No significant difference was found between the genders according to the NMP-Q score (p>0.05). Those carrying chargers, spending time with a smartphone before bedtime, and checking their smartphones as soon as they wake up had a higher NMP-Q score (p<0.01). NMP-Q score increased with the increase in the duration of using smartphones, daily usage time, daily frequency of checking smartphones, and daily mobile internet usage time (p<0.001). Conclusion: It may be helpful to delay the age of starting smartphone use as much as possible to reduce the level of nomophobia in university students since those who started using smartphones at an earlier age are more prone to nomophobia. mobile
Keywords: Nomophobia; university; students; mobile phone